2017
DOI: 10.1002/ehf2.12203
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of cardiac troponin T level in patients with cardiac amyloidosis

Abstract: AimThe aim of this study was to evaluate the diagnostic utility of high‐sensitivity cardiac troponin T (hs‐cTnT) levels in discriminating cardiac amyloidosis from patients with cardiac hypertrophy caused by aetiologies other than cardiac amyloidosis.Methods and resultsSerum hs‐cTnT levels were measured in 96 patients with cardiac amyloidosis (light chain: 23, wild‐type transthyretin amyloidosis: 40, and mutated transthyretin amyloidosis: 33), and 91 patients with other causes of cardiac hypertrophy who were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 34 publications
2
66
1
3
Order By: Relevance
“…cardiac hypertrophy (optimal cutoff value 0.0312 ng/mL; sensitivity, 74%; specificity, 79%). 8 We developed an index for predicting 99 m Tc-PYP positivity by adding 1 point for each of the 3 factors. Patients with more points had a higher rate of being 99 m Tc-PYP positive.…”
Section: Diagnostic Approach To Ttr-ca Using 99 M Tc-pyp Scintigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…cardiac hypertrophy (optimal cutoff value 0.0312 ng/mL; sensitivity, 74%; specificity, 79%). 8 We developed an index for predicting 99 m Tc-PYP positivity by adding 1 point for each of the 3 factors. Patients with more points had a higher rate of being 99 m Tc-PYP positive.…”
Section: Diagnostic Approach To Ttr-ca Using 99 M Tc-pyp Scintigraphymentioning
confidence: 99%
“…1 In addition, we have previously reported that high serum levels of high-sensitivity cardiac troponin T (hs-cTnT) are highly suggestive of CA, allowing its differentiation from cardiac hypertrophy of other etiologies. 8 Therefore, we hypothesized that a combination of biochemical (laboratory examination), physiological (ECG), and structural (echocardiography) findings could raise the pretest probability of diagnosing TTR-CA with 99 m Tc-PYP scintigraphy. The aim of this study was to evaluate the characteristics of patients who are 99 m Tc-PYP-positive and make recommendations about patient selection for 99 m Tc-PYP scintigraphy to diagnosis TTR-CA in the elderly using minimally invasive and widely used examinations such as hs-cTnT, ECG, and echocardiography.…”
mentioning
confidence: 99%
“…High levels of hs-cTnT were suggestive of cardiac amyloidosis (cut-off value: 0.0312 ng/mL, sensitivity: 0.74, specificity: 0.76, area under the curve: 0.788; 95% confidence interval: 0.723-0.854, p < 0.001), compared to BNP and E/e 0 ratio. These results indicated that that further refined diagnostic approaches including imaging modalities and histopathological examination, are needed for patients with increased hs-cTnT level to avoid underdiagnosis of CA [11].…”
Section: Biochemical Analysismentioning
confidence: 92%
“…In fact, native T1 and ECV are also elevated in patients in whom conventional clinical testing and LGE imaging suggested no cardiac involvement, thereby highlighting a potential role as an early disease marker [16]. In addition, their ability to track various markers of disease activity, such as cardiac function and blood biomarkers, signifies their correlation with the severity of CA [16]. Moreover, the assessment of native T1 and ECV aids riskstratifying patients with CA [17], which may add incremental value over the existing clinical markers.…”
Section: T1 Mappingmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH) was not considered as an inclusion criterion in their study. On the other hand, we mainly performed 99 m Tc-PYP scintigraphy with a suspicion of ATTR-CM among patients with LVH and persistent hypertroponinemia according to previous research carried out by Takashio et al 3 Therefore, suspicion of ATTR-CM. Expanding our cohort, we again evaluated the score of the Kumamoto criteria in 438 consecutive patients aged ≥70 years who simultaneously underwent electrocardiography, echocardiography and high-sensitivity cardiac troponin T analysis from April 2019 to October 2019.…”
mentioning
confidence: 99%